Mobile Right Atrial Thrombi in a Patient with the Hemoglobin SC Disease. (19th July 2011) - Savage, H. O.; Ding, N.; Eso, O.; Sachdev, B.; Lefroy, D. L.
Abstract : The formation of Intracardiac thrombi is rare in the absence of structural heart disease or atrial fibrillation. We describe a case of spontaneous right atrial thrombus formation that occurred in a patient with a hypercoagulable condition who had been sub optimally anticoagulated.